Organizational and economic mechanism and development strategy for the restoration of the liberated territories of Azerbaijan in the post-conflict period - Mammadov, M.; Mammadova, F.; Ganiyev, Kh.; Nagdiyev, O.; Мамедов, М.; Мамедова, Ф.; Ганієв, Х.; Нагдієв, О. (Харківський національний автомобільно-дорожній університет, 2021)
The article examines the economic reforms carried out in Azerbaijan, the goals outlined by industries according to Strategic Plan of the “Strategic Road Map for the National Economy and Main Sectors of the Economy”, aimed at implementing these reforms, development strategies, and reforms carried out in accordance with State Programs. The importance of these reforms in the national economy sustainable and constant development has been noted. The article describes the development of the non-oil sector in the framework of general, sectoral and regional programs adopted in Azerbaijan to achieve sustainable development, diversification of the economy, development of infrastructure aimed at ensuring socio-economic development. Thus, the level of gas supply infrastructure in the regions, the level of gasification, the level of industrialization, the creation and development of infrastructure in existing industrial zones, as well as the implementation of clustering measures were reviewed and determined that in 2019, 46 enterprises were registered as residents and more than 8,000 permanent jobs were created. At the same time, during the 4th stage of the industrial revolution, the implementation of innovations in the field of ICT in Azerbaijan, new opportunities for sustainable development of the country as a result of digitalization and the formation of a digital economy were created. Also, the importance of restoring the liberated territories of the country, assessing the current state of the economy, determining the priorities of the sectors and establishing an organizational-management mechanism that ensures the gradual development of these areas in a timely manner were studied in detail. The relevant state decrees, defining measures that need to be taken to ensure the restoration and development of the Upper Karabakh and Kelbajar-Lachin regions and adjacent territories, were also considered and analyzed, specific directions of the organizational and management mechanism to ensure their implementation were specified.
Організаційно-економічний механізм та стратегія розвитку відновлення визволених територій Азербайджану у постконфліктний період
Keywords: reforms; strategic; roadmap; politics; sustainable development; regional development; development strategies; restoration; development concept; реформи; стратегічна дорожня карта; політика; сталий розвиток; регіональний розвиток; стратегії розвитку; відновлення; концепція розвитку; 640.5.658; 10.30977/ЕТК.2225-2304.2021.38.0.45